DYSPHAGIA IN PEOPLE WITH INTELLECTUAL DISABILITIES - Mirza Sitarevic; Leila Begic; Valentina Misanovic (Human Research in Rehabilitation, 2021)
People with intellectual disabilities often face a number of disorders that can impair their health and even endanger their lives. One of these disorders is dysphagia, which is often unrecognized in this population. The main goal of the research was to determine the differences in the severity of dysphagia relation to the degree of intellectual disability in persons placed in institutional accommodation. The study involved 31 respondents diagnosed with intellectual disabilities. The results showed that people with a higher degree of intellectual disability have more pronounced dysphagia. Caregivers of people with intellectual disabilities should be aware of the presence of dysphagia in people with intellectual disabilities, and refer them to a speech-language pathologist in a timely manner with the goal of timely diagnosis and treatment to improve the overall health and quality of life of people of this population.